Developing Sustainable Community Partnerships. Lessons Learned from the University of Georgia’s Archway Partnership - Rebecca Nesbit; Stacy Jones (Transylvanian Review of Administrative Sciences, 2025)
This article describes the University of Georgia’s Archway Partnership—one of the university’s community outreach efforts based on its land grant mission—and the process that it uses to develop and sustain a community partnership. In particular, the article focuses on Archway’s use of a neutral, professional facilitator as a means of creating and sustaining the characteristics associated with successful, sustained university/ community partnerships, particularly cooperative goal setting, shared power, group cohesion, and partnership management. Using administrative data on the Archway Partnership and qualitative survey data from Archway faculty, the article highlights critical success factors associated with the Archway Partnership’s relationship building, thus helping to unpack the black box of how to develop a successful university/ community partnership.